2022
DOI: 10.3389/fenrg.2022.847818
|View full text |Cite
|
Sign up to set email alerts
|

MgO-Coated Layered Cathode Oxide With Enhanced Stability for Sodium-Ion Batteries

Abstract: Na0.67Ni0.33Mn0.67O2 is a prospective layered cathode material for sodium-ion batteries owing to its low cost, ease of synthesis, and high specific capacity. However, due to direct contact with electrolytes during the cycling process, the cyclic stability is not satisfied. To address this issue, magnesium oxide (MgO) surface modification was performed in this study to improve the material’s cycling properties. MgO layers of various thicknesses were successfully coated onto the cathode, and their electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Similarly, the TiO 2 coating can suppress surface reactions on an O3-NaMn 0.33 Fe 0.33 Ni 0.33 O 2 cathode and improve its structural stability. [135] Besides, the integrity of the lattice and cycling stability of layered oxide cathodes can be maintained by ZrO 2 [50,136] or MgO [137] coating.…”
Section: Oxide Coating Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the TiO 2 coating can suppress surface reactions on an O3-NaMn 0.33 Fe 0.33 Ni 0.33 O 2 cathode and improve its structural stability. [135] Besides, the integrity of the lattice and cycling stability of layered oxide cathodes can be maintained by ZrO 2 [50,136] or MgO [137] coating.…”
Section: Oxide Coating Layermentioning
confidence: 99%
“…[ 132 ] (b) Structural evolution near the surface of the NaMCNB electrode. Reproduced with permission: Copyright 2020, Elsevier B.V. [ 138 ]…”
Section: Modulation Technologiesmentioning
confidence: 99%
“…3,4 However, layered metal oxide materials mainly suffer from problems of poor cycling stability due to irreversible phase conversion and interfacial side reactions with electrolytes. 5 The modification of layered oxide cathodes primarily focuses on the design of electrode materials, such as element doping, 6−8 surface coating, 9,10 nanostructure design, 11,12 O/P phase mixture, 13,14 and so on. Recently, due to their pivotal role as transport media in SIBs, both the electrolyte and its interphase with the electrode are receiving more and more scholarly focus.…”
Section: Introductionmentioning
confidence: 99%
“…Oxide coating, which is a common approach in other cathode materials, , has been rarely explored in O3-NaCrO 2 . However, a recent study by Wang et al showed the positive effect of in-situ-generated Cr 2 O 3 layers on the cyclic stability of O3-NaCrO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, pitchderived carbon-coated O3-NaCrO 2 showed the highest cyclic stability, with approximately 90% of its initial capacity retained after 300 C/D cycles. 19 Oxide coating, which is a common approach in other cathode materials, 31,32 has been rarely explored in O3-NaCrO 2 . However, a recent study by Wang et al showed the positive effect of in-situ-generated Cr 2 O 3 layers on the cyclic stability of O3-NaCrO 2 .…”
Section: ■ Introductionmentioning
confidence: 99%